2017
DOI: 10.1007/s11604-017-0664-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of unexpected emergency diseases using FDG-PET/CT in oncology patients

Abstract: Although rare, an unexpected emergency disease requiring urgent management can be detected using FDG-PET/CT in oncology patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…DFSP can also present high SUVmax [ 15 ]. Most reports about hematoma and lymph node metastasis focus on detection of lesions but not on differentiation with other diseases, so they did not list data of SUVmax [ 16 , 17 ]. SUVmax of hematoma and lymph node metastasis has been reported as 3.4 and 6.3, but we still need more evidence [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…DFSP can also present high SUVmax [ 15 ]. Most reports about hematoma and lymph node metastasis focus on detection of lesions but not on differentiation with other diseases, so they did not list data of SUVmax [ 16 , 17 ]. SUVmax of hematoma and lymph node metastasis has been reported as 3.4 and 6.3, but we still need more evidence [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal CT plays the most important role in the diagnosis of ileus. Abdominal CT can not only identify the site that causes ileus but also predict the pathophysiology of the ileus with the symbolic signs such as closed loop sign [5], beak sign [6], whirl sign [7], and dirty fat sign [8]. Contrast-enhanced CT can further depict the ischemic changes of the affected intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no ideal diagnostic tool that can be used alone to provide a definite and accurate diagnosis before surgery. Research efforts to find and introduce non-invasive, inexpensive and practically usable laboratory methodologies that do not depend on the user's experience in the diagnosis of AA are still ongoing [13]. AA is a well-known infection and inflammation.…”
Section: Gallium-68 Citrate Pet/ct Findings In An Experimental Model mentioning
confidence: 99%
“…Previous studies have reported the use of Indium-111 and 99m Tc-HMPAO-labelled leukocyte scintigraphy, 99m Tc-labelled human immune globulin and anti-granulocyte antibodies in AA cases [10,11]. In recent years, incidental cases of AA have been identified during 18 F-FDG PET/CT scans for oncologic screening [12][13][14][15]. One of the most popular agents used for infection and inflammation nuclear imaging is Gallium-67 ( 67 Ga), which has been used for imaging purposes for the past 40 years [16].…”
Section: Gallium-68 Citrate Pet/ct Findings In An Experimental Model mentioning
confidence: 99%